Kombinovani ortodontski i hiruški tretman impaktiranog maksilarnog očnjaka kod mladog pacijenta sa malokluzijom klase II: prikaz slučaja - Pašagić, Ljubica; Ilić, Ivana; Kecman, Vesna; Bulajić, Marko; Zubović, Nina; Glišić, Branislav (Scripta Medica, 2020)
The impaction of maxillary canines is one of the biggest challenges in orthodontics practice. This case report describes successful surgical and orthodontic approach to the treatment of palatally impacted maxillary canine in a 14-year-old boy. Intraoral clinical examination revealed an absence of the upper right canine, an ectopic position of the upper left canine and crowding in the maxillary arch. The impaction of right maxillary canine and class II malocclusion were confirmed by lateral cephalogram, orthopantomogram and cone beam computed tomography. In the first phase, a transpalatal arch to the upper first molar teeth was applied, first premolars were extracted, and brackets were placed on all teeth and nickel-titanium arch wire was applied. The initial orthodontic phase was soon thereafter followed by the surgical exposure and orthodontic traction of the impacted canine using ligature wire attached from the button with chain to the open coil on the arch wire. The orthodontic treatment took two years with satisfactory aesthetic and functional results at the end. This clinical case has shown that adequate treatment of impacted maxillary canine can be achieved by using combined surgical technique and appropriate orthodontic approach.